Eksplorasi Etnomatematika Pada Makanan Khas Tumbu’ Bugis - Sakinah, Durrah; Lubis, Ilham Ismail; Habibi, Mhmd (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
Culture-based education holds significant value as a tool and strategy for individuals and society in the information and technology age. Consequently, the researchers aim to explore ethnomathematics in typical Bugis food called Tumbu' Bugis. This study employed a qualitative method, utilizing an ethnographic approach and involving local communities familiar with the research study, specifically the Bugis tribe. Through observation and interviews, it was found that the typical food of Tumbu' Bugis contains the concept of geometry on the leaves used as Tumbu' wrappers and on the shape of Tumbu'. The concept of 3D shapes was also found, especially tubes (cylinders). In addition, there is also an algebraic concept in Tumbu' regarding the number of leaves needed to make Tumbu' and the number of Tumbu wrappers produced in one banana leaf. Tumbu' can be used as a medium for learning mathematics in plane geometry, including the properties and area of circumference and rectangular shapes. Comparison materials may also involve Tumbu' Bugis specialties. In conclusion, the typical food of Tumbu' Bugis encapsulates mathematical concepts, facilitating the teaching and learning process for teachers and students, ultimately aiding in achieving learning goals.